TRIM5α Promotes Ubiquitination of Rta from Epstein–Barr Virus to Attenuate Lytic Progression - Huang, Hsiang-Hung; Chen, Chien-Sin; Wang, Wen-Hung; Hsu, Shih-Wei; Tsai, Hsiao-Han; Liu, Shih-Tung; Chang, Li-Kwan (Frontiers in Microbiology, 2017)
Replication and transcription activator (Rta), a key protein expressed by Epstein-Barr virus (EBV) during the immediate-early stage of the lytic cycle, is responsible for the activation of viral lytic genes. In this study, GST-pulldown and coimmunoprecipitation assays showed that Rta interacts in vitro and in vivo with TRIM5α, a host factor known to be involved in the restriction of retroviral infections. Confocal microscopy results revealed that Rta colocalizes with TRIM5α in the nucleus during lytic progression. The interaction involves 190 amino acids in the N-terminal of Rta and the RING domain in TRIM5α, and it was further found that TRIM5α acts as an E3 ubiquitin ligase to promote Rta ubiquitination. Overexpression of TRIM5α reduced the transactivating capabilities of Rta, while reducing TRIM5α expression enhanced EBV lytic protein expression and DNA replication. Taken together, these results point to a critical role for TRIM5α in attenuating EBV lytic progression through the targeting of Rta for ubiquitination, and suggest that the restrictive capabilities of TRIM5α may go beyond retroviral infections.